Pengaruh Kreativitas Dan Kedisiplinan Terhadap Prestasi Belajar Siswa Kelas Xi Di Smk Telkom Bandung (Studi Kasus Pada Siswa Kelas Xi Teknik Komputer Jaringan Telekomunikasi Smk Telkom Bandung): Creativity, Discipline, Learning Achievement, Student, SMK Telkom Bandung - Fauzan, Adzani Haikali; Rizaldi, Arjuna (JEMBA, 2024)
This study aims to test the effect of creativity and discipline on learning achievement of class XI telecommunication computer network engineering students at SMK Telkom Bandung and to find out creativity, discipline, and learning achievement class XI telecommunication network computer engineering students partially or simultaneously at SMK Telkom Bandung. This study employs a quantitative technique togetherwith descriptive and verification methods. The analysis method used in this research is multiple linear equations using SPSS v23 application and hypothesis testing statistical tests t test and f test. The results of this study show that creativity, discipline and learning achievement are generally in the good category. The results of hypothesis testing show that Creativity has a positive and significant partial effect on Learning Achievement. The results of hypothesis testing show that Discipline has a positive and significant effect on Learning Achievement in part. The results of hypothesis testing show that Creativity and Discipline have a positive and significant effect on Learning Achievement simultaneously.